The Pathogenesis of Eosinophilic Asthma: A Positive Feedback Mechanism That Promotes Th2 Immune Response via Filaggrin Deficiency - Gao, Wei; Gong, Jiuyu; Mu, Mi; Zhu, Yujin; Wang, Wenjuan; Chen, Wen; Han, Guojing; Hu, Hong; Bao, Pengtao (Frontiers in Immunology, 2021)
Eosinophilic asthma is a common subtype of asthma and often progresses to severe disease. In order to understand its pathogenesis, targeted next-generation gene sequencing was performed on 77 Chinese EA patients and 431 Chinese healthy controls to obtain differential genomic variations. Among the 41 Single Nucleotide Polymorphisms screened for mutation sites in greater more than 3 patients, filaggrin gene FLG rs192116923 T>G and FLG rs75235053 C>G were newly found to be associated with EA patients with atopic dermatitis and severe EA, respectively. Filaggrin has been shown to be mainly expressed in epithelial cells and plays an important role in the formation of an effective skin barrier. Bioinformatic analysis indicated FLG rs192116923- T>G may increase the binding of Smad3 to transmit TGF-β1 signaling, and thereby inhibit Filaggrin expression, and FLG rs75235053 C>-G may add new splicing sites to reduce filaggrin monomers. It has been known that the level of Th2 cytokine IL-4 was is increased in EA patients, and IL-4 increased airway epithelial permeability and enhanced inflammatory response through some unclear mechanisms. To figure out whether filaggrin was is involved in immune responses in asthma, we have treated human respiratory epithelial cell line BEAS-2B cells with IL-4 and found that the expression levels of filaggrin and E-cadherin decreased significantly in a time and dose-dependent manner, suggesting that IL-4 increased airway epithelial permeability by reducing filaggrin and adhesion molecules. In addition, in our study, IL-4 increased the expression of epithel-derived inflammatory cytokines IL-33 and TSLP which further enhanced the Th2 inflammatory response. To investigate the role of FLG filaggrin in development of EA, knockdown filaggrinFLG with siRNA revealed a decrease in E-cadherin levels, which were further down-regulated by IL-4 stimulation. Knockdown of FLG filaggrin alone did not affect the levels of IL-33 and TSLP, but further exacerbated the decrease of IL-33/TSLP caused by IL-4, suggesting that FLGfilaggrin may involve in IL-4R signaling pathway to regulate the level of IL-33/TSLP. In conclusion, in the Th2 cytokine milieu of asthma, FLG deficient mutation in airway epithelial cells may increase the epithelial permeability and the expression of IL-33/TSLP which positively feedback the Th2 inflammation response.